Analisis Resepsi Mahasiswa Ilmu Komunikasi Universitas Semarang Terhadap Tayangan Iklan Televisi Layanan SMS Premium Versi Ramalan Paranormal - Febrian, Febrian (Jurnal The Messenger, 2012)
This study aims to understand the audience reception of cultural horoscope, forecasts and the occult are sold through premium SMS services. Basic theory used in this study is the cultivation theory of McQuail (1996) which states that television become a major tool in which the media or the television audience to learn about society and culture environment. In other words, the perception of what our minds awakened about society and culture is largely determined by the television. The research method qualitative descriptive used is a   interpretive perspective. Research was conducted in the city of Semarang. Informants in this study were students of the University of Semarang science communication. Concluded that the analysis of other research has answered this reception, where there are three positions in the analysis of audience reception that is the position of the dominant readings, readings that are negotiated and oppositional readings. From this study it can be concluded if the ad is a Premium SMS content that contents can not be held responsible, this can be seen from the researcher interviewed informants in the field.